Gamified Digital Learning with Wordwall: An Experimental Study on Grammar Achievement - Yuliana Dewi Sulianto; Eliasanti Agustina; Endang Mastuti Rahayu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the effect of using the Wordwall application as Digital Gamification Media on the grammar achievement of tenth-grade students. Many students struggle with constructing correct sentences due to monotonous learning methods that fail to motivate them. To address this issue, the study employed Wordwall, an interactive digital game-based learning technology designed to enhance the engagement and effectiveness of grammar instruction. The study employed a quantitative research approach with a proper experimental design, including a pre-test and post-test. The population of this study consisted of all 10th-grade students at SMAN 1 Wringinanom, totaling 418 individuals across 11 classrooms, including a special class of 38 pupils. The study included 38 students from class X-1 as the experimental group and 38 students from class X-2 as the control group. The researcher employed cluster random sampling to select the sample. Data collection was conducted through pre-tests and post-tests. The results showed a significant effect in the experimental group's grammar performance, with the mean score increasing from 67.16 to 82.42, while the control group's score rose from 63.68 to 70.47. Statistical analysis confirmed data normality and a significant difference in post-test scores (p < 0.05), indicating that the use of Wordwall positively impacted students’ grammar achievement. Based on the analysis, the null hypothesis (H0) was rejected, indicating a significant difference between the experimental and control groups. Consequently, the alternative hypothesis (Ha) was accepted, confirming that the treatment or intervention applied in the study had a measurable impact on student outcomes. This means that the use of the Wordwall application affected grammar achievement.